Enhancing lower passing, confidence, and motivation through cooperative learning: the impact of team game tournaments in volleyball learning - Kharisma, Yudhi; Ginanjar, Agi; Wahyuni, Tri; Anggraeni, Reni (Edu Sportivo: Indonesian Journal of Physical Education, 2025)
Background: Physical Education (PE) teachers often face challenges such as lack of mastery of underarm passing techniques, low self-confidence, and students’ motivation in volleyball games. By using Cooperative Learning (CL) type Team Games Tournament (TGT), we can overcome existing challenges. This study complements existing research by looking at the effect of TGT on passing and motivation, as well as self-confidence that has never been discussed at all in junior high school students and presents a CL fidelity model of TGT type that has never been discussed at all. Research Objectives: The study aims to examine the effect of the Team Games Tournament (TGT) type cooperative learning model on junior high school students’ lower passing ability, confidence, and motivation in volleyball. Methods: This study used a one-group pretest-posttest experimental design to evaluate changes in 20 students selected by purposive sampling. The research instrument used a volleyball underhand passing skill test, a self-confidence questionnaire for junior high school students in PE learning on volleyball underhand passing material, and a motivation questionnaire for junior high school students in PE learning. The data analysis technique used statistical descriptions, paired sample t-tests, and one-way ANOVA. Finding/Results: The findings and results of this study state that the fidelity model of TGT is at a very good level in implementation and planning. TGT has an influence on underhand passing, self-confidence, and learning motivation of junior high school students with results on underhand passing being better than self-confidence, and motivation. Conclusion: This study concludes that there is an influence of TGT on volleyball underhand passing, self-confidence, and motivation in junior high school students. Further research to update the research instruments used and pay attention to the fidelity model for the use of TGT, updating research instruments, and comparison classes to make them more generalisable.